Ultra-Thin/Wide-Band Polarization Conversion Metasurface and Its Applications in Anomalous Reflection and RCS Reduction - Xuewen Li; Yuxiang Wang; Jingdao Fan; Jiahao He; Xiaojun Huang (Applied Sciences, 2022)
In this paper, the design of an ultra-wideband polarizer based on a metasurface with high-performance is reported and demonstrated. The polarizer is composed of a dielectric substrate with double semicircular gap patches and a metal film. Multiple strong resonance points enable the design to convert the incident linearly polarized waves into cross-polarized waves in the 14.8–28.0 GHz range, with a fractional bandwidth of 61.7% and a corresponding polarization conversion rate (PCR) above 95%. Further simulated results show that the PCR remains above 87% in the 14.37–24.75 GHz range when the incident angle of the electromagnetic (EM) waves is between 0–30°, and the physical mechanism is explained by the surface current distribution. In addition, the gradient metasurface is designed according to the Pancharatnam–Berry phase principle to achieve anomalous reflection, and the 1-bit metasurface is coded to reduce the Radar Cross Section (RCS). The EM waves reach an anomalous reflection of −23° at 15 GHz normal incidence, and the RCS is reduced by 10 dB in the range of 15.3–28.0 GHz. These findings have potential application value in stealth and antenna design.